The changing microbiome of poultry meat; from farm to fridge. (October 2021) - Marmion, M.; Ferone, M.T.; Whyte, P.; Scannell, A.G.M.
Abstract: Chickens play host to a diverse community of microorganisms which constitute the microflora of the live bird. Factors such as diet, genetics and immune system activity affect this complex population within the bird, while external influences including weather and exposure to other animals alter the development of the microbiome. Bacteria from these settings including Campylobacter and Salmonella play an important role in the quality and safety of end-products from these birds. Further steps, including washing and chilling, within the production cycle aim to control the proliferation of these microbes as well as those which cause product spoilage. These steps impose specific selective pressures upon the microflora of the meat product. Within the next decade, it is forecast that poultry meat, particularly chicken will become the most consumed meat globally. However, as poultry meat is a frequently cited reservoir of zoonotic disease, understanding the development of its microflora is key to controlling the proliferation of important spoilage and pathogenic bacterial groups present on the bird. Whilst several excellent reviews exist detailing the microbiome of poultry during primary production, others focus on fate of important poultry pathogens such as Campylobacter and Salmonella spp. At farm and retail level, and yet others describe the evolution of spoilage microbes during spoilage. This review seeks to provide the poultry industry and research scientists unfamiliar with food technology process with a holistic overview of the key changes to the microflora of broiler chickens at each stage of the production and retail cycle. Highlights: The microflora of fresh chicken meat affects the safety and quality of the end-product. Steps from hatching to meat packaging induce selective pressures on the microbiota. Processing steps affect the abundance and diversity of bacterial phyla and genera. Processing-related pressures select for stress-tolerant populations.